2016
DOI: 10.1007/s40808-016-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling the side weir discharge coefficient using neural network

Abstract: Weirs are common structures that are widely used in the almost water engineering projects such as hydropower systems, irrigation and drainage networks along with sewage networks. A side weir has many possible uses in hydraulic engineering and has been investigated as an important structure in hydro systems, as well. In this paper, predicting the discharge coefficient of side weirs (Cd sw) was considered using the empirical formulas, multilayer perceptron (MLP) and radial basis function (RBF) neural network as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The soft computing technique is one of the most relevant and modern techniques used in the civil engineering problems (Sihag et al 2018b, c;Nain et al 2018bKisi et al 2017;Parsaie et al 2017c;Kisi et al 2015;Parsaie and Haghiabi 2014;Shiri and Kisi 2012). In this investigation, GP, SVM and M5P tree models were used.…”
Section: Soft Computing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The soft computing technique is one of the most relevant and modern techniques used in the civil engineering problems (Sihag et al 2018b, c;Nain et al 2018bKisi et al 2017;Parsaie et al 2017c;Kisi et al 2015;Parsaie and Haghiabi 2014;Shiri and Kisi 2012). In this investigation, GP, SVM and M5P tree models were used.…”
Section: Soft Computing Techniquesmentioning
confidence: 99%
“…Tiwari et al (2017) used the generalised regression neural network, MLR, M5P model tree and SVM to predict the cumulative infiltration of soil and found that SVM works well than the other techniques. Various researchers have been used various soft computing techniques in hydraulics and environmental engineering applications (Sihag et al 2017b(Sihag et al , c, 2018aHaghiabi et al 2018;Nain et al 2018a;Tiwari et al 2018;Parsaie et al 2017a, b;Shiri et al 2016Shiri et al , 2017Parsaie andHaghiabi 2015, 2017;Parsaie 2016;Azamathulla et al 2016;Baba et al, 2013). These researchers found that these techniques work exceptionally well.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high cost of experiments and de ciency in laboratory studies due to simpli cations and limit range of measured parameters, researchers attempt to use the mathematical approaches for modeling and predicting the scour depth at downstream of ip buckets. In the eld of mathematical modeling, using both of CFD and soft computing techniques was reported by Xiao et al [11].Nowadays, by advancing the soft computing techniques in the most areas related to hydraulic engineering, investigators have tried to use these techniques for predicting the scouring phenomena [12][13][14][15][16][17][18][19], speci cally scour depth at downstream of ip bucket. In this regard, using the Arti cial Neural Networks (ANNs), Genetic Programming (GP), Support Vector machine and M5 Model Tree, Group Method of Data Handling (GMDH), and Adaptive Neuro Fuzzy Inference System (ANFIS) can be mentioned [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…These formulas have dependable performance for calculating the discharge in normal channel but when floods occur, surplus flow on the capacity of the normal channel flow in floodplains makes using the classical formulas for estimating the discharge of flow unsure. Using them may lead to errors (Ackers 1993;Al-Khatib et al 2012, 2013Azamathulla et al 2016;Dehdar-behbahani and Parsaie 2016;Parsaie and Haghiabi 2014;Parsaie and Haghiabi 2015a, b, c). Several reasons have been reported for the lack reliability of these methods under flood conditions (Bousmar and Zech 1999).…”
Section: Introductionmentioning
confidence: 99%